2013
DOI: 10.1158/1078-0432.ccr-12-2853
|View full text |Cite
|
Sign up to set email alerts
|

A Potent Combination of the Novel PI3K Inhibitor, GDC-0941, with Imatinib in Gastrointestinal Stromal Tumor Xenografts: Long-Lasting Responses after Treatment Withdrawal

Abstract: Introduction Oncogenic signaling in gastrointestinal stromal tumors (GIST) is sustained via PI3K/AKT pathway. We used a panel of six GIST xenograft models to assess efficacy of GDC-0941 as single agent or in combination with imatinib (IMA). Experimental design Nude mice (n=136) were grafted bilaterally with human GIST carrying divers KIT mutations. Mice were orally dosed over four weeks, grouped as follows: A) control; B) GDC-0941; C) IMA and D) GDC+IMA treatments. Xenografts re-growth after treatment discon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
81
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 36 publications
10
81
0
Order By: Relevance
“…A growing body of evidence now suggests that targeting multiple pathways by means of combination treatment may be a more beneficial approach. Given the success observed with PI3K inhibitors in combination with IM in GIST models (13,14), we set out to examine the effects of combined inhibition of AKT (a downstream effector of PI3K) and KIT in a panel of IM-sensitive and -resistant GIST cell lines. We selected MK-2206, a highly selective, allosteric, pan-AKT inhibitor for our combination studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A growing body of evidence now suggests that targeting multiple pathways by means of combination treatment may be a more beneficial approach. Given the success observed with PI3K inhibitors in combination with IM in GIST models (13,14), we set out to examine the effects of combined inhibition of AKT (a downstream effector of PI3K) and KIT in a panel of IM-sensitive and -resistant GIST cell lines. We selected MK-2206, a highly selective, allosteric, pan-AKT inhibitor for our combination studies.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical trials are currently underway to investigate the use of PI3K/AKT inhibitors in combination with RTK inhibitors in CLL, melanoma, and NSCLC. Recently, PI3K inhibitors were combined with IM in preclinical studies using GIST xenografts, and this combination demonstrated superior and more durable responses as compared to either single agent (13,14). Reduced or absent expression of the phosphatase and tensin homolog (PTEN) was significantly associated with IM treatment in GIST patient samples, and PTEN deficiency in vitro results in hyperactivation of AKT (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Recent preclinical in vivo studies performed on GIST xenografts, using PI3K inhibitors in combination with imatinib, indicated synergistic and long-lasting effects, and suggested that PTEN inactivation could have an impact on the response to this therapy. 11,12 Yet, currently no studies have been performed to investigate the range of PTEN abnormities in imatinib-resistant GIST patients.…”
mentioning
confidence: 99%